Village Financial Management In Teluk Kenidai Village, Tambang District, Kampar Regency In 2020 - Salsabila, Friscilla; Marta, Auradian (Future Science, 2023)
The problem in this research is the planning and budgeting are not following the needs of the community, in terms of implementation they have not been able to realize the budget and do not prioritize important programs with existing finances, this is also caused by the lack of quality human resources in Teluk Kenidai Village. The purpose of this study is to find out and describe the process of financial governance and the factors that influence financial management in Teluk Kenidai Village, Tambang District, Kampar Regency in 2020. The approach in this research is to use a qualitative approach and the type of research is descriptive. The research location was carried out in Teluk Kenidai Village, Tambang District, Kampar Regency, using data collection techniques through interviews and documentation. The results showed that financial management in Teluk Kenidai Village, Tambang District, Kampar Regency was not optimal. Judging from the planning, it has not set a priority scale, so the people's needs are not met. In terms of implementation, it has not realized all that was planned. Then the reporting and accountability have not been carried out promptly, this is due to the lack of quality human resources.